Compositions, colours and efficiencies of organic–inorganic lead iodide/bromide perovskites for solar cells. (November 2014) - Davies, M. L.; Carnie, M.; Holliman, P. J.; Connell, A.; Douglas, P.; Watson, T.; Charbonneau, C.; Troughton, J.; Worsley, D.
Abstract : Developments in the field of organic–inorganic lead halide perovskite based solar cells have metaphorically opened the door to an exciting new solid state photovoltaic technology that retains the low cost and processability benefits of dye sensitised solar cells (DSCs). Encouraging device efficiencies of greater than 10% on both titania and alumina, and as a planar device, have been reported in the literature. Here we report the characteristics of a series of lead iodide/bromide perovskites. As one might expect, changing the halide(s) alters the crystal structure and band gap of the perovskite which results in the possibility of vivid and colourful solar cells; a characteristic which is seen as one of the main benefits of DSCs. X-ray diffraction and scanning electron microscopy with elemental mapping via energy dispersive X-ray analysis has been used to characterise perovskites on sensitised thin films. UV-vis and diffuse reflectance has been used to study the optical characteristics of crystallised perovskite thin films. Finally device performance is evaluated and suitability for use in photovoltaic devices is discussed.